Artificial lactation by exogenous hormone treatment in non-pregnant sows - Michiko NOGUCHI; Takehito SUZUKI; Reiichiro SATO; Yosuke SASAKI; Kazuyuki KANEKO (The Society for Reproduction and Development, 2020)
This study aimed to determine if lactation can be induced by exogenous hormonal treatment in non-pregnant sows. In experiment 1, pseudopregnant animals were divided into four groups and given: 1) 5 mg of estradiol dipropionate (EDP) 5 days before (n = 4), 2) 5 mg of EDP 10 days before (n = 3), 3) 10 mg of EDP 5 days before (n = 3) or 4) 10 mg of EDP 10 days (n = 3) before PGF2α treatment. Artificial lactation was induced in seven pseudopregnant sows (53.8%) by exogenous hormonal treatment. There was no significant effect of either an increased EDP dosage or interval from the EDP treatment to PGF2α treatment on the induction rate of artificial lactation. In experiment 2, milk samples were collected from artificial lactating and natural lactating sows (n = 6). IgG and IgA levels in the milk collected from both groups were significantly associated with time during the experimental period. Milk IgG levels 24 h after PGF2α treatment in artificial lactating sows were higher than those in the colostrum of lactating sows. In experiment 3, hormonal profiles in pseudopregnant sows with (n = 3) or without (n = 3) EDP treatment were determined. There was a significant difference in estradiol-17β levels on days 8, 7 and 5 before PGF2α treatment between groups. Progesterone and prolactin concentrations did not differ between groups. The present study revealed for the first time that lactation could be induced by exogenous hormonal treatment in non-pregnant sows and that the milk collected from these sows contained high immunoglobulin levels.